Gut Microbiota Dysbiosis and Increased Plasma LPS and TMAO Levels in Patients With Preeclampsia - Wang, Jing; Gu, Xunke; Yang, Jing; Wei, Yuan; Zhao, Yangyu (Frontiers in Cellular and Infection Microbiology, 2019)
Objective: To characterize the gut microbiota in patients with preeclampsia (PE) compared with healthy controls. Methods: We analyzed and compared the microbiota communities in the feces of 48 PE patients with 48 age-, gestational weeks-, and pre-pregnancy body mass index-matched healthy controls using 16S rRNA gene sequencing, and also we tested fecal and plasma lipopolysaccharide (LPS) and plasma trimethylamine-N-oxide (TMAO) concentration levels in the two groups. Results: Compared with the control group, microbial alpha diversity was lower in the PE group, but there was no statistically significant difference between the two groups. At the phylum level, Firmicutes (51.64% PE vs. 59.62% Control, P < 0.05), Bacteroidetes (40.51% PE vs. 34.81% Control, P< 0.05), Proteobacteria (4.51% PE vs. 2.56% Control, P < 0.05), and Actinobacteria (2.90% PE vs. 1.77% Control, P < 0.05), exhibited significant differences between the PE group and the control group. LEfSe analysis found 17 differentially abundant taxa between the two groups. PICRUSt analysis found that in the KEGG pathways, the microbial gene functions related to LPS biosynthesis were higher in the fecal microbiome of the PE group. The fecal and plasma LPS concentrations and plasma TMAO concentrations of PE patients were higher than those of the healthy controls. Conclusion: PE patients had gut microbiota dysbiosis and increased plasma LPS and TMAO levels, which will lead to a better understanding of the relationship between the gut microbiota and PE.